Cost and efficacy comparison of prenatal recall and reflex DNA screening for trisomy 21, 18 and 13 - Bestwick, Jonathan Paul (PLoS One, 2019)
OBJECTIVE: To compare costs and efficacy of reflex and recall prenatal DNA screening for trisomy 21, 18 and 13 (affected pregnancies). In both methods women have Combined test markers measured. With recall screening, women with a high Combined test risk are recalled for counselling and offered a DNA blood test or invasive diagnostic testing. With reflex screening, a DNA analysis is automatically performed on plasma collected when blood was collected for measurement of the Combined test markers. METHODS: Published data were used to estimate, for each method, using various unit costs and risk cut-offs, the cost per woman screened, cost per affected pregnancy diagnosed, and for a given number of women screened, numbers of affected pregnancies diagnosed, unaffected pregnancies with positive results, and women with unaffected pregnancies having invasive diagnostic testing. RESULTS: Cost per woman screened is lower with reflex v recall screening: £37 v £38, and £11,043 v £11,178 per affected pregnancy diagnosed (DNA £250, Combined test markers risk cut-off 1 in 150). Reflex screening results in similar numbers of affected pregnancies diagnosed, with 100-fold fewer false-positives and 20-fold fewer women with unaffected pregnancies having invasive diagnostic testing. CONCLUSIONS: Reflex DNA screening is less expensive, more cost-effective, and safer than recall screening.